Job Application Interest of Final Year Students: The Influence of Employer Branding, Perception of Career Development, and Work Environment: Minat Melamar Kerja Mahasiswa Tingkat Akhir: Pengaruh Employer Branding, Persepsi Pengembangan Karier, dan Lingkungan Kerja - Ramadlan, A.Alfi Syahri; Nasrullah, Muhammad Hafidh; Sundari, Ariefah (Academia Open, 2026)
General Background: Competition for talent requires organizations to strengthen their attractiveness as employers by aligning organizational attributes with candidate expectations. Specific Background: Final-year students represent a critical group transitioning into the labor market, evaluating employer branding, perceived career development, and work environment when forming job application intentions. Knowledge Gap: Prior studies show inconsistent findings and rarely integrate these three variables simultaneously, particularly within non-metropolitan higher education contexts. Aims: This study analyzes the relationships among employer branding, perceived career development, and work environment in shaping job application intentions among final-year students. Results: Using quantitative explanatory analysis of 194 responses, all instruments were valid and reliable (Cronbach’s alpha > 0.93), and the model explained 94.90% of variance. Simultaneously, all variables were significant; however, only perceived career development (β = 0.457; p = 0.001) and work environment (β = 0.505; p = 0.000) showed significant positive effects, while employer branding was not significant when tested alongside other variables. Novelty: This study introduces an integrated model emphasizing concrete organizational attributes over symbolic corporate image in explaining job application intentions. Implications: Findings indicate that students prioritize career growth opportunities and supportive work environments, suggesting organizations should design employer value propositions focused on career clarity and conducive workplace conditions rather than relying solely on employer branding. Highlights• Career growth perception becomes primary determinant of application decisions• Workplace conditions outperform symbolic organizational reputation signals• Integrated variables jointly explain very high behavioral variance KeywordsEmployer Branding; Career Development; Work Environment; Job Application Intention; Students